Does lack of control lead to conspiracy beliefs? A meta‐analysis. (23rd June 2020) - Stojanov, Ana; Halberstadt, Jamin
Abstract: Perceived lack of control is widely believed to motivate, at least partly, belief in conspiracy theories. We question the theoretical foundations of this belief and meta‐analyze existing published and unpublished studies to assess the overall effect of lack of control on conspiracy beliefs. The overall effect was small and not statistically significant ( d  = −0.05), and was not moderated by comparison group (baseline vs. control affirmation), type of manipulation used to threaten control, inclusion of a manipulation check, or sample type. However, the predicted effect of control was more likely to be observed when beliefs were measured in terms of specific conspiracy theories, rather than as general or abstract claims. Overall, the present studies to date offer limited support for the hypothesis that conspiracy beliefs arise as a compensatory control.